1988
DOI: 10.1159/000153791
|View full text |Cite
|
Sign up to set email alerts
|

DNA Haplotypes and Frameworks Associated with the Beta-Globin Gene in the Kachari Population of Assam (India)

Abstract: DNA haplotypes and frameworks associated with the β-globin gene were determined in a Tibeto-Burman group, the Kachari, from Upper Assam, India, using restriction analysis at eight restriction sites. Of the total of 59 subjects, 26 were homozygous for HBB*A and 33 homozygous for HBB*E. Complete haplotype determination in 33 subjects revealed a conspicuous difference in haplotype distribution between HBB*A- and HBB*E-bearing chromosomes. The Southeast Asian HBB*E -associated haplotype – + –+ + + +– (27–2 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Since these two frameworks differ at positions, 70 nucleotides to the 5′ side of the β E mutation and 382 nucleotides to the 3′ side of it, their data suggested the existence of atleast two independent origins of the β E mutation in Southeast Asia. As per their findings hemoglobin associated haplotype 27-2 is the most common in Southeast Asia (Thailand) and the presence of the same haplotype among the Kachari population of Northeast India suggests single origin of HbE in Thailand and Assam (Hundrieser et al 1988). Deka et al (1988) once suggested that in case of multiple mutational events, a second mutant might have its origin in the Tibeto-Burman population of Assam.…”
Section: Origin and Spread Of Hemoglobin Ementioning
confidence: 77%
“…Since these two frameworks differ at positions, 70 nucleotides to the 5′ side of the β E mutation and 382 nucleotides to the 3′ side of it, their data suggested the existence of atleast two independent origins of the β E mutation in Southeast Asia. As per their findings hemoglobin associated haplotype 27-2 is the most common in Southeast Asia (Thailand) and the presence of the same haplotype among the Kachari population of Northeast India suggests single origin of HbE in Thailand and Assam (Hundrieser et al 1988). Deka et al (1988) once suggested that in case of multiple mutational events, a second mutant might have its origin in the Tibeto-Burman population of Assam.…”
Section: Origin and Spread Of Hemoglobin Ementioning
confidence: 77%
“…The de mographic analyses of some Bodo popu lations have suggested different selective mechanisms in Assam and in Thailand [Deka, 1981;Das and Deka, 1985;Deka et al, 1988]. On the other hand, there are reports on two different mutations of Hb E with two different DNA frame works [Antonarakis et al, 1982;Hundrieser et al, 1988]. In this report the re sults of a study of the Hb E gene fre quency in three endogamous populations of the northern part of West Bengal, who are offshoots of the Bodo group, are dis cussed in the light of this background knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…These would thus seem to be separate mutations, since in addition there is no evidence of gene flow from Southeast Asia. However, Hundreiser et al (1988a) have found the same haplotype as one of these European families in Assam and suggest that there may have been gene flow from India. Two other populations have high frequencies of hemoglobin E: The Eti-Turks in Southeast Turkey and the Veddas of Sri Lanka.…”
Section: Distributions Of P-globin Mutants Other Than Hemoglobin Smentioning
confidence: 69%
“…This distribution suggests that the hemoglobin E mutation and/or intense endemic malaria originated in this central area of Southeast Asia and diffused out from there. Hundreiser et al (1988a) have found that the major haplotype and the framework (No.2) associated with the pE-globin gene in Assam is the same as those associated with it in Thailand. The PE genes in Cambodia are found on both frameworks 2 and 3 (Hundreiser et al, 1988b), and there is a cline with a n increase in framework 3 haplotypes eastward away from Thailand.…”
Section: Distributions Of P-globin Mutants Other Than Hemoglobin Smentioning
confidence: 92%